Establishing Safe Extra-articular Parameters for Cortical Button Distal Fixation During Ulnar Collateral Ligament Reconstruction. Issue 11 (September 2019) - Hooper, Perry O.; Warren, Jared; Silko, Christopher; Frangiamore, Salvatore J.; King, Dominic; Farrow, Lutul D.; Schickendantz, Mark S.
Background: A variety of methods exist for fixation during ulnar collateral ligament (UCL) reconstruction on the ulna for the overhead throwing athlete. Current biomechanical evidence suggests that cortical button fixation may fail at a higher load and under more cycles than interference screw fixation alone, while also minimizing the risk of fracture. A safe angle for placement of this cortical button has not yet been determined. Purpose: To define a safe angle for cortical button deployment during UCL reconstruction to avoid violation of the proximal radioulnar joint (PRUJ). Study Design: Descriptive laboratory study. Methods: Measurements on 100 cadaveric ulna bones, 50 women and 50 men, were obtained referencing the entry point for ulnar fixation, which is 1 cm distal to the ulnar humeral joint line along the medial UCL ridge. Ulnar width at the entry point and distance to the PRUJ were obtained to calculate safe distal angulation, while distance from the entry point to the posterior ulnar crest ulnarly and distance from the PRUJ to the posterior ulnar crest radially were obtained to calculate safe posterior angulation. Ten bony measurements on the same group of specimens were performed by 3 authors to establish an interobserver reliability. Means, quartiles, and outliers were obtained for the calculated angles. Finally, recommended angles of entry were determined to be approximately 1 interquartile range above the upper limit. Results: The mean distal angle of entry that was obtained was 11.32° (SD, ±4.80°; 95% CI, 10.37°-12.27°; P < .001). Three upper limit outliers were discovered: 24.20°, 23.4°, and 21.1°. The mean posterior angle of entry was 40.44° (SD, ±6.18°; 95% CI, 39.22°-41.67°; P < .001). There were no outliers for the posterior angle of entry. Interobserver reliabilities were strong for the 4 measurements. Conclusion: To be safely outside of the PRUJ utilizing a cortical button construct, we recommend 30° distal angulation and 60° posterior angulation for ulnar fixation during UCL reconstruction. Both parameters are 1 quartile above the highest calculated angle of entry. Clinical Relevance: These data define safe parameters for distal fixation during UCL reconstruction and highlight a clear entry point for reference.